Four new combinations of the genera Bulbophyllum and Dendrobium (Orchidaceae) from the Philippines - Naive, Mark Arcebal K. (Universidad de Costa Rica, 2019)
Three new combinations under the genus Bulbophyllum and one new combination under the genus Dendrobium are proposed. This work is aimed to solve the ambiguity in the Philippine Orchidaceae. Keywords: Epidendroideae, Malesian flora, Mindanao, plant taxonomy, tropical botany